2020
DOI: 10.1016/j.copsyc.2019.06.037
|View full text |Cite
|
Sign up to set email alerts
|

The socioecology of social class

Abstract: Influence of social class on thought and behavior depends on specifics of social context • This is because people compare themselves with others on locally relevant dimensions • Context shapes the relevance of social comparison dimensions (e.g., education, income, ethnicity) and also the outcomes of such comparisons • Differences in income are more predictive of social and political attitudes in countries with high economic inequality • Differences in education are more predictive of social and political attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
12
0
3
Order By: Relevance
“…Furthermore, a meta‐analysis found that the average effect size of stereotype threat manipulations on women's maths performance is smaller in contexts that have smaller gender based attainment gaps in mathematics (Picho et al., 2013). This is presumably because women's gender identity is more positive and perceived as more compatible with academic success in contexts that have smaller gender gaps (see also Manstead, Easterbrook, & Kuppens, 2020).…”
Section: The Identities In Context Model: Linking Contextual Variatiomentioning
confidence: 99%
“…Furthermore, a meta‐analysis found that the average effect size of stereotype threat manipulations on women's maths performance is smaller in contexts that have smaller gender based attainment gaps in mathematics (Picho et al., 2013). This is presumably because women's gender identity is more positive and perceived as more compatible with academic success in contexts that have smaller gender gaps (see also Manstead, Easterbrook, & Kuppens, 2020).…”
Section: The Identities In Context Model: Linking Contextual Variatiomentioning
confidence: 99%
“…We empirically test predictions derived from the identities in context model which suggest that historical performance of SES groups will moderate the association between students’ socioeconomic background and their identity compatibility (Easterbrook & Hadden, 2021). Sociocultural variables such as a group’s relative performance can signal the value or status of that group within the relevant context, and so contribute to the content and meaning of their social identities (Manstead et al, 2020; Uskul & Oishi, 2020). Within a school, a large socioeconomic attainment gap is likely to act as a signal indicating that students from lower socioeconomic groups are not expected to do well in education and that educational success is something that members of low SES groups are unlikely to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…These results presumably arise because, in contexts with smaller attainment gaps, the lower status group members are less threatened and perceived their social identities as more compatible with academic success. This leaves less scope for social psychological interventions that target social identity processes to improve academic performance (see also Easterbrook & Hadden, 2021; Manstead et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These moderators demonstrate the importance of understanding the wider context in which self-affirmations are implemented and, in particular, recognizing how the context can determine which groups are likely to be experiencing threat and are thus likely to benefit from selfaffirmation interventions (Binning & Browman, 2020;Easterbrook & Hadden, 2021;Manstead et al, 2020). Critically, however, there has yet to be an empirical demonstration that threat moderates (or mediates) the effectiveness of self-affirmation interventions in education, as proxies for social identity threat are often operationalized as objective indicators of group membership (e.g., ethnicity or eligibility for free school meals, but see Celeste et al, 2021;Layous et al, 2017).…”
Section: Moderatorsmentioning
confidence: 99%
“…Within large, multi-school studies, these contextual factors should be measured so that this contextual variation can be demonstrated empirically. Indeed, we suggest that identifying and measuring variables that objectively characterize the local or national context may be a particularly fruitful avenue for researchers to follow (e.g., Celeste et al, 2021;Easterbrook et al, 2019;Manstead et al, 2020), as may using alternative sources to quantify the context, such as aggregating questionnaire responses (Yeager et al, 2019), interviews with teachers (Gehlbach et al, 2016), or computing measures of student discrepancies from their classmates (Benish-Weisman et al, 2020).…”
Section: Moderatorsmentioning
confidence: 99%